The Role of Rubrics in Fair Assessment Practices - Picón-Jácome, Edgar (Íkala, Revista de Lenguaje y Cultura, 2013)
In this article, I support the thesis that utilizing rubrics, discussed and agreed upon teachers and students, guarantees the promotion of fair assessment practices. This claim is supported by the argument that designing and applying scoring rubrics enhances validity and transparency in evaluation, while their consensual design supports democracy, promotes positive washback and facilitates equitable assessment practices—all of them principles inherent to fairness. A concept of rubric that integrates an authentic task and its scoring scale, applied as an alternative assessment procedure within a critical approach, is emphasized.